SISTEM INFORMASI BUDIDAYA IKAN LELE DI BALAI BENIH IKAN (BBI) BUNGUS - Nurmaliana Pohan; Suciati Kartika Chandra; Febriyen Doris (Program Studi Teknik Informatika Universitas Nusa Putra, 2021)
The Bungus Fish Seed Center as an institution that produces catfish seeds has developed good cultivation techniques and management of catfish farming businesses. This study aims to examine catfish farming techniques and the application of information systems in the management of catfish farming at the Bungus Fish Seed Center. The research method used is a mixed research method by means of observation, interviews, and documentation. The results showed that the Bungus Fish Seed Center applied good cultivation techniques, such as managing water quality, selecting superior seeds, using good and correct feed, and good pond maintenance techniques. The Bungus Fish Seed Center also implements an information system in managing catfish farming, such as a real-time monitoring system for catfish production, a pond water quality monitoring system, a feed recording system, a production cost calculation system, and a planning and production system as well as financial reporting. From the results of the analysis and design of catfish farming information systems, it can be concluded that information systems can provide benefits for catfish farmers in managing catfish farming businesses more effectively and efficiently. Thus, catfish farming at the Bungus Fish Seed Center has implemented good cultivation techniques. So that it is expected to make a positive contribution in increasing the productivity and quality of catfish and the economy in Indonesia.